Gender differences in social risk taking - Friedl, Andreas; Pondorfer, Andreas; Schmidt, Ulrich (Journal of economic psychology, 2020)
•We perform a lab experiment to analyze gender differences in social risk taking.•Women turn out to be more risk averse than men in social risk taking.•We can show that high inequality aversion of women causes this result.•A second experiment in a small-scale society finds no gender differences.•This shows that gender differences in social risk taking are culture-specific. Women in Western societies are typically more risk averse than men in individual risk taking decisions. In real life, however, risk taking decisions are usually made in a social context. So far, empirical evidence whether gender differences are also present in the social risk taking domain is missing. We use a controlled experiment to analyze gender differences in social risk taking. We find that inequality aversion is the main driver for risk aversion in social risk taking. Disaggregating the data for males and females shows that this effect is mainly driven by strong inequality aversion of women. Moreover, by running the experiment with non-standard subjects from an egalitarian small-scale society, our results suggest that gender differences in social risk taking are culture-specific.